Pengendalian penyakit hawar (lateblight) pada Kentang (Solanum tuberosum L.) melalui penerapan solarisasi tanah dan aplikasi agen hayati Trichoderma harzianum - Eirene Brugman; Endang Dwi Purbajanti; Eny Fuskhah (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
The purpose of the research was to assess the effectiveness of soil solarization and biological agent Trichoderma harzianum application in controlling lateblight disease caused by Phytophthora infestans on potato. The experiment was assigned in a split plot design with soil solarization as main plot and the density of Trichoderma harzianum as sub-plot. Soil solarization treatment consisted of solarization (A1) and non-solarization (B1). Density of Trichoderma harzianum used is B1(control)= 0g, B2 = 10g (107 cfu/l), B3 = 20g (2 x 108 cfu/l), B4 = 30g (3 x 108 cfu/l) and B5 = 40 g (4 x 108 cfu/l). Soil solarization treatment is carried out by using transparent polyethylene sheets with a thickness of 45 µm. Parameters measured were soil temperature, intensity level of pathogen attack, the rate of infection and total yield. Data were subjected to ANOVA and followed by LSD test. Soil solarization for 4 weeks increase the soil temperature by 7,6oC and significantly increase the production of potato by 14.28%. Application of biological agent Trichoderma harzianum on level B4 30g (3 x 108 cfu /L) gives the best results in reducing the the intensity level of pathogen attack by 69.13% and the rate of disease infection into 1,012 unit/day. The results of this research may provide benefical information in the future for plant protection activities. Keywords : P.infestans, Trichoderma harzianum, soil solarization, potato